KOMPARATIF HASIL BELAJAR MODEL ENE DAN TS DENGAN MEMPERHATIKAN AQ SISWA - Dwi Wulan Dini; Raden Gunawan Sudarmanto; Tedi Rusman (JEE (Jurnal Edukasi Ekobis), 2014)
The method used in this study is a comparative study with the experimental approach. Hypothesis test is using two variants of path analysis and t-test for two independent samples. Based on the analysis of the data it obtained: 1) there are significant differences in the learning results of economics lesson that students use a model learning ENE and TS. 2) there are interactions between the learning model with adversity intelligence students on economic subjects. 3) there is no difference between the learning results of the economic study the lesson that students use a model learning ENE and TS to adversity high level of intelligence. 4) there is a difference between the learning results of the economic study the lesson that students use a model learning ENE and TS for the level of intelligence of the adversity medium. 5) there is a difference between the economic study results of students who are learning the lesson that uses the model ENE and TS adversity low intelligence level.Metode yang digunakan dalam penelitian ini adalah studi banding dengan pendekatan eksperimen. Tes hipotesis menggunakan analisis varian dua jalan dan t-test dua sample independen. Berdasarkan analisis data diperoleh: 1) Ada perbedaan signifikan hasil belajar ekonomi siswa yang pembelajarannya menggunakan model ENE danTS. 2) Ada interaksi antara model pembelajaran dengan kecerdasan adversitassiswa pada mata pelajaran ekonomi. 3) Tidakada perbedaanhasil belajar ekonomi antara siswa yang pembelajarannya menggunakan model ENE danTSuntuk tingkat kecerdasan adversitas tinggi.4) Ada perbedaan hasil belajar ekonomi antara siswa yangpembelajarannya menggunakan model ENE danTSuntuk tingkat kecerdasan adversitas sedang. 5) ada perbedaan hasil belajar ekonomi antara siswa yang pembelajarannya menggunakan model ENE danTSpada tingkat kecerdasan adversitas rendah.Kata kunci: aq, ene, hasil belajar, ts.